Physiological Response of Lettuce (Lactuca sativa L.) Grown on Technosols Designed for Soil Remediation - Mateo González-Quero; Antonio Aguilar-Garrido; Mario Paniagua-López; Carmen García-Huertas; Manuel Sierra-Aragón; Begoña Blasco (Plants, 2024)
This study focuses on the physiological response of lettuce grown on Technosols designed for the remediation of soils polluted by potentially harmful elements (PHEs: As, Cd, Cu, Fe, Pb, and Zn). Lettuce plants were grown in five treatments: recovered (RS) and polluted soil (PS) as controls, and three Technosols (TO, TS, and TV) consisting of 60% PS mixed with 2% iron sludge, 20% marble sludge, and 18% organic wastes (TO: composted olive waste, TS: composted sewage sludge, and TV: vermicompost of garden waste). The main soil properties and PHE solubility were measured, together with physiological parameters related to phytotoxicity in lettuce such as growth, photosynthetic capacity, oxidative stress, and antioxidant defence. All Technosols improved unfavourable conditions of PS (i.e., neutralised acidity and enhanced OC content), leading to a significant decrease in Cd, Cu, and Zn mobility. Nevertheless, TV was the most effective as the reduction in PHEs mobility was higher. Furthermore, lettuce grown on TV and TO showed higher growth (+90% and +41%) than PS, while no increase in TS. However, lower oxidative stress and impact on photosynthetic rate occurred in all Technosols compared to PS (+344% TV, +157% TO, and +194% TS). This physiological response of lettuce proves that PHE phytotoxicity is reduced by Technosols. Thus, this ecotechnology constitutes a potential solution for soil remediation, with effectiveness of Technosols depending largely on its components.